INDONESIA'S ATTITUDE IN FACING THE SOUTH CHINA SEA CONFLICT, POLICY ANALYSIS AND IMPLICATIONS - Irianto, Bambang Sugeng; Sutrisno, Sutrisno (EQUALEGUM International Law Journal, 2024)
Background. The South China Sea conflict is one of the complex and challenging geopolitical issues in the Southeast Asia region. This study aimed to analyze Indonesia's attitude in dealing with this conflict, with a focus on foreign policy and its implications for regional stability. Research Method. This research uses a type of legal research that is normative in nature (normative legal research) and through a foreign policy analysis approach. Findings. The factors are diplomacy and negotiation policy, Indonesia's role in ASEAN, efforts to strengthen maritime cooperation, external actor involvement, the need for a just and sustainable settlement, impact on regional stability, and protection of national maritime interests that influence Indonesia's attitudes and the strategies taken by the Indonesian government in managing this conflict. The impact of Indonesia's attitude towards political and security dynamics in the Southeast Asia region. Conclusion. Indonesia has an important strategic role to play in addressing the South China Sea conflict as the largest maritime nation in Southeast Asia. Indonesia's presence in regional diplomacy and efforts to mediate the conflict are key to achieving a sustainable solution.